From Africa to Jamaica and back: the Atlantic as a dynamic linguistic contact zone - Hollington, Andrea (Revista do GEL, 2021)
This paper is concerned with Africa and the African Diaspora in Jamaica from a linguistic perspective. It will shed light on linguistic and communicative practices which illustrate the dynamic and reciprocal relationship between Africa and the Caribbean. My objective is to go beyond the approach of traditional (Caribbean) creolistics, which usually investigates African “substrate” influences in so-called creole languages, and to look at the Atlantic contact area as a dynamic zone with mutual and multidirectional influences. This will involve not only the historical dimension of the Transatlantic Slave Trade, through which the African Diaspora in Jamaica, the Caribbean, and the Americas emerged in the first place, but also a focus on the role of the dynamicity of current language practices on identity, language ideologies, linguistic creativity, and agency. An important aspect in this respect is the emblematicity of African elements, as linguistic elements, which are different from ‘Standard English’ (often perceived as the colonial language and the language of the slave master and oppressor), and which are marked in the context of conscious linguistic choices. Moreover, there is an awareness of the African heritage in Jamaican language practices that informs conscious efforts to use African linguistic elements (for instance, names). For many Jamaicans, their African heritage and identity play an important role. This can be observed, in particular, in Rastafari discourses and in Reggae music and culture, which emphasize a strong focus on Africa. These phenomena are also relevant in (Anglophone) Africa, where Jamaican linguistic practices are adopted through the influence of Reggae, Dancehall, and Rastafari. Therefore, this contribution will also feature some examples of how influences from the Diaspora come back to Africa, for example, in music and youth language practices.